Reporting Helicopter Emergency Medical Services in Major Incidents: A Delphi Study - Fattah, Sabina; Johnsen, Anne Siri; Sollid, Stephen J M; Wisborg, Torben; Rehn, Marius; HEMS Major Incident Reporting Collaborators; Sóti, Ákos; Truhlář, Anatolij; Krüger, Andreas J; Gunnarsson, Björn; Gryth, Dan; Ohlén, David; et al. (Air medical journal, 2016)
OBJECTIVE: Research on helicopter emergency medical services (HEMS) in major incidents is predominately based on case descriptions reported in a heterogeneous fashion. Uniform data reported with a consensus-based template could facilitate the collection, analysis, and exchange of experiences. This type of database presently exists for major incident reporting at www.majorincidentreporting.net. This study aimed to develop a HEMS-specific major incident template. METHODS: This Delphi study included 17 prehospital critical care physicians with current or previous HEMS experience. All participants interacted through e-mail. We asked these experts to define data variables and rank which were most important to report during an immediate prehospital medical response to a major incident. Five rounds were conducted. RESULTS: In the first round, the experts suggested 98 variables. After 5 rounds, 21 variables were determined by consensus. These variables were formatted in a template with 4 main categories: HEMS background information, the major incident characteristics relevant to HEMS, the HEMS response to the major incident, and the key lessons learned. CONCLUSION: Based on opinions from European experts, we established a consensus-based template for reporting on HEMS responses to major incidents. This template will facilitate uniformity in the collection, analysis, and exchange of experience.
Keywords: delfská metoda; urgentní zdravotnické služby; výzkumná zpráva; Air Ambulances; Databases, Factual; Research Report; konsensus; databáze faktografické; Consensus; Humans; Physicians; lidé; letecká záchranná služba; lékaři; Delphi Technique; Evropa; Emergency Medical Services; Europe